Panggilan dan Perutusan Paulus Sebagai Rasul Dalam Teks Galatia 1:11-24 dan Relevansi Bagi Mahasiswa STIPAS Keuskupan Agung Kupang - Denaor, Paulus Suyono; Mali, Andreas Yosep; Wea, Maria Elviana; Done, Donatus; Buik, Petronela; Hingan, Yasinta Mou; Suri, Mario Krisanto; S. Senda, Siprianus; M. Kanaf, Gregorio Antonio (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This paper aims to discuss the call and mission of Paul as an apostle in the text of Galatians 1: 11-24 and its relevance for STIPAS of Kupang Archdiocese students. Paul's call is seen as a divine call that fundamentally changed his life, showing that God's call has extensive transformational power. In addition, Paul's calling requires perseverance and the guidance of the Holy Spirit, teaching students to live in dependence on God and face challenges with courage. Relevance for STIPAS of Kupang Archdiocese students includes spiritual development, inclusivity, and dependence on the Holy Spirit in their ministry. Therefore, understanding and appreciation of Paul's call is an important foundation for STIPAS of Kupang Archdiocese students in preparing themselves to become faithful spiritual leaders in proclaiming the Gospel.